Agriculture in a more uncertain global trade environment. (16th June 2022) - Anderson, Kym
Abstract: The global trade environment is more uncertain now than it has been for decades. In the short term, bilateral trade "wars" and the COVID‐19 pandemic have added to longer‐term uncertainties such as sporadic national policy responses to climate change, to the digital revolution, to up‐scaled assertiveness and economic coercion by rapidly growing China, and to antiglobalization groups. The underlying concerns could be reduced through greater multilateral cooperation, but that has been in short supply in recent years, not least because of eroding support for globalization. This article re‐examines the case for greater unilateral openness to agricultural trade in the wake of uneven economic growth and structural transformation as food systems respond to this increased uncertainty and to growing pressures for agriculture to become more sustainable and for food to be safer and more nutritious. The article concludes by pointing to better policy options than trade measures for achieving most national objectives—options that can simultaneously benefit the rest of the world in terms of easing natural resource and environmental stresses while supporting economic growth and reducing national and global poverty, food and nutrition insecurity, and inequalities in income, wealth, and health.